The role of incline, performance level, and gender on the gross mechanical efficiency of roller ski skating - Sandbakk, Øyvind; Hegge, Ann M.; Ettema, Gertjan (Frontiers in Physiology, 2013)
The ability to efficiently utilize metabolic energy to produce work is a key factor for endurance performance. The present study investigated the effects of incline, performance level and gender on the gross mechanical efficiency during roller ski skating. Thirty-one male and nineteen female elite cross-country skiers performed a 5-min submaximal session at approximately 75% of VO2peak on a 5% inclined treadmill using the G3 skating technique. Thereafter, a 5-min session on a 12% incline using the G2 skating technique was performed at a similar work rate. Gross efficiency was calculated as the external work rate against rolling friction and gravity divided by the metabolic rate using gas exchange. Performance level was determined by the amount of skating FIS points (the Federation of International Skiing approved scoring system for ski racing) where fewer points indicate a higher performance level. Strong significant correlations between work rate and metabolic rate within both inclines and gender were revealed (r=-0.89-0.98 and P